EXPERIENCE OF USING COMPUTER BRONCHOPHONOGRAPHY IN PEDIATRIC PRACTICE - Makhpieva Guldonakhon Kabiljanovna (Scholar Express Journals, 2025)
Thanks to innovative developments in the field of information technology, computer acoustic diagnostics is beginning to be actively introduced into clinical practice. Computer bronchophonography is one of the promising domestic developments in the field of methods for assessing the functional state of the respiratory system. This method can be used at any stage of medical care to identify bronchial obstruction, monitor the effectiveness of treatment and preventive measures for bronchopulmonary pathology, which is especially important in early and preschool age. However, further research is required in this area, which is relevant both from a scientific and practical point of view.
Keywords: children; respiratory function; respiratory acoustics